Konsepsi Pengendalian Diri dalam Perspektif Psikologi Sufi dan Filsafat Stoisisme: Studi Komparatif dalam Buku Karya Robert Frager dan Henry Manampiring - Dinella Irawati Fajrin; Hasan Mud’is; Yulianti Yulianti (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Self-control based on spiritual elements can be said to be the cause of human obstruction in achieving peace and happiness. Thus, this study aims to uncover the concept of self-control in the perspective of sufi psychology and stoicism philosophy that is able to answer the problems of life today in achieving peace and happiness. In its preparation, this article uses qualitative methods with a library approach and is analyzed comparatively. The results and discussions of this study include an explanation of self-control in Robert Frager's view, self-control in the philosophy of stoicism, and a comparison of the concepts of self-control from both views. From this study, it can be concluded that the philosophy of Stoicism and Sufi psychology shake hands to agree that the most basic self-control is controlling perception, so that one can achieve a peaceful and peaceful life. Association with God is the main purpose of self-control in sufi psychology to get a life that is surrounded by a sense of peace. Stoicism philosophy emphasizes that man can distinguish between things that they can control or those they cannot control.